The weaver mutation of GIRK2 results in a loss of inwardly rectifying K+ current in cerebellar granule cells. - Surmeier, D J (1996)
The weaver mutation in mice results in a severe ataxia that is attributable to the degeneration of cerebellar granule cells and dopaminergic neurons in the substantia nigra. Recent genetic studies indicate that the GIRK2 gene is altered in weaver. This gene codes for a G-protein-activated, inwardly rectifying K+ channel protein (8). The mutation results in a single amino acid substitution (glycine-->serine) in the pore-forming H5 region of the channel. The functional consequences of this mutation appear to depend upon the co-expression of other GIRK subunits--leading to either a gain or loss of function. Here, we show that G-protein-activated inwardly rectifying K+ currents are significantly reduced in cerebellar granule cells from animals carrying the mutant allele. The reduction is most pronounced in homozygous neurons. These findings suggest that the death of neurons in weaver is attributable to the loss of GIRK2-mediated currents, not to the expression of a nonspecific cation current.